Reproduksi Kultural Komunitas Sastra “Pawon Sastra” Di Surakarta, Jawa Tengah - Dwi Susanto; Susanto; Bagus Kurniawan (Institut Teknologi Sepuluh Nopember, 2019)
Pawon Sastra's literary community in Surakarta in contexts of Surakartaurban culture has conducted cultural and social practices. It brings impactsand responses from society. The main topic of this research is social andcultural practices carried out by the Pawon Sastra community as a form ofreciprocal relations with the structure surrounding it which similar to theinteraction between the structure and agent. This research used thesociological point of view especially using the agents, construction, andactions. The problems of this research are (1) how the agent responds to thesocial structure and (2) what kind of cultural practices are manifested by theagent, and (3) what impact arises as to the result of the cultural practices bythe agent. The research was carried out using a qualitative method. The dataused were the activities of the literary community, the results of their work,and the subjects involved in the community. The results of this studyindicated that social practices were carried out in various ways such aspublishing, the reinterpretation of traditions, or publications as a form ofinteraction among similar communities. Moreover, the impact on socialstructures was the increase in the formation of the same communities and theemergence of new individuals who follow the footsteps of Pawon Sastra. Thisis also enhanced by various interactions occurring in the social environmentof the newly established community.